Hydrogen peroxide and Helicobacter pylori extract treatment combined with APE1 knockdown induce DNA damage, G2/M arrest and cell death in gastric cancer cell line - Manoel-Caetano, Fernanda S. [UNESP]; Rossi, Ana Flávia T. [UNESP]; Ribeiro, Marcelo Lima; Prates, Janesly [UNESP]; Oliani, Sonia Maria [UNESP]; Silva, Ana Elizabete [UNESP] (Elsevier, 2020)
Chronic inflammation resulting from Helicobacter pylori (H. pylori) infection, the major risk factor for gastric cancer, results in increased release of reactive oxygen species (ROS), promoting oxidative stress and DNA damage. APE1 endonuclease, a key component of the base excision repair (BER) pathway, is responsible for the repair of damage induced by ROS. However, the APE1 gene and other DNA damage response (DDR) genes are still poorly understood in gastric cancer. Thus, we aimed to investigate whether the silencing of APE1 by shRNA can interfere with the survival of AGS gastric cancer cells after treatment with hydrogen peroxide (H2O2) and/or H. pylori extract (HPE) and its relation with the expression of DDR genes (ATM, ATR, and H2AX) and miRNAs that target DDR genes. In the AGS cells expressing APE1, isolated or combined treatment with H2O2 and HPE promoted a slight increase in the cell proliferation and increased the levels of intracellular ROS and DNA double strand breaks (DSBs) indicated by ©H2AX foci, a reduction in the proportion of cells in the G0/G1 phase and an increase in the initial apoptosis rate. Moreover, upregulation of APE1, ATR, miR-15a, miR-21, miR-24 and miR-421 and downregulation of ATM and H2AX was observed. In silenced AGS cells after treatment with H2O2 alone or combined with HPE, we observed an increase in the cell proliferation rate and the levels of intracellular ROS and DSBs and a reduction in the proportion of cells in S and G2/M phase arrest, leading to late apoptosis. APE1 knockdown also caused a reduction in the expression of ATM and miR-421, while ATR expression was increased. Based on our results, APE1 knockdown may promote changes in cellular processes by increasing genomic instability, leading to G2/M arrest and cell apoptosis, so it may be a promising strategy for controlling tumor progression.
Keywords: AGS cell line; APE1 knockdown; DNA damage; DNA repair; Helicobacter pylori; Hydrogen peroxide